1994
DOI: 10.1002/jbm.820280114
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclastic resorption of calcium phosphates is potentiated in postosteogenic culture conditions

Abstract: Cell-mediated resorption of densely sintered hydroxyapatite (HA1250), tricalcium phosphate (TCP), and 600 degrees or 900 degrees C calcined hydroxyapatite (HA600 and HA900, respectively), was investigated by using two culture systems. The first was an osteoclastic cell culture, and the second was a two-stage culture that was composed of a bonelike tissue formation on the substrata in the first stage and its subsequent resorption by osteoclasts in the second stage. Neither of the materials showed resorption or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 16 publications
1
59
0
1
Order By: Relevance
“…16 However, plasma-sprayed HA-coated implant material has some problems, such as the low adhesive strength of the coating substrate interface and biodegration or bioresorption. 5 In order to cope with these problems, Ishizawa et al developed a method of forming a thin HA layer by means of anodization and hydrothermal treatment. Commercially pure titanium is anodized in an electrolytic solution of dissolved ␤-GP and CA to form an AOFCP on the surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 However, plasma-sprayed HA-coated implant material has some problems, such as the low adhesive strength of the coating substrate interface and biodegration or bioresorption. 5 In order to cope with these problems, Ishizawa et al developed a method of forming a thin HA layer by means of anodization and hydrothermal treatment. Commercially pure titanium is anodized in an electrolytic solution of dissolved ␤-GP and CA to form an AOFCP on the surface.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Furthermore, such implant materials have been researched and developed with regard to early osseointegration, and it has been demonstrated that plasma-sprayed hydroxyapatite (HA) coating on Ti implant materials enhances rapid bone formation because of their osteoconductive property compared with uncoated Ti implant materials. However, such problems as low adhesive strength of the coating substrate interface and significant biodegradation or bioresorption 5 have not been resolved. In order to cope with these problems, the Nikon Corporation improved the surface characteristics of Ti even further by developing a HA layer on the outer most surface, that is to say, the formation of an anodic Ti oxide film containing calcium and phosphate (AOFCP) by anodizing titanium in an aqueous electrolytic solution containing ␤-glycerophosphate and calcium acetate dissolved in water.…”
Section: Introductionmentioning
confidence: 97%
“…The acidic microenvironment produced by osteoclasts and the surface of the mate- rials may be responsible for the degradation of these particles. 13,14 Furthermore, the activity of well-polarized multinucleated giant cells for ACC resorption may be enhanced. These findings are in agreement with those of previous studies in which sintered hydroxyapatite was shown to be resorbed by osteoclasts.…”
Section: Discussionmentioning
confidence: 98%
“…These findings are in agreement with those of previous studies in which sintered hydroxyapatite was shown to be resorbed by osteoclasts. 13,15 Osteologic was commercially developed for the measurement of osteoclast resorbing activity. 6 However, Osteologic is difficult to use for cytochemical analysis of activated osteoclasts because of the thick opaque crystal glass.…”
Section: Discussionmentioning
confidence: 99%
“…Carbonate apatite (CAP) is resorbed by osteoclasts 1,2) and is similar in biocompatibility to hydroxyapatite (HAP) 3) and β-tricalcium phosphate (β-TCP) 4) . Although the bioresorption mechanism of CAP may be different from that of β-TCP 5) , CAP dissolves to the same extent as β-TCP in weak acid media 1) .…”
Section: Introductionmentioning
confidence: 99%